Magnetic recoverable Ag3PO4/Fe3O4/γ-Fe2O3 nanocomposite - Jenifer Vaswani Reboso; Jaime Sadhwani Alonso; Dunia E. Santiago (Desalination and Water Treatment)
The use of nanomaterials in water treatment is an alternative for the development of new systems to optimize the purification process. Heterogeneous photocatalysis is used for the treatment of wastewaters contaminated with recalcitrant pollutants that cannot be removed with conventional wastewater treatment techniques. Silver phosphate (Ag3PO4) can be used in visible-light driven photocatalysis. An important challenge of heterogeneous photocatalysis is to find a proper support for the photocatalysts to reduce the expense associated with the separation and reuse of these materials. However, the immobilization of the catalyst leads to lower reaction rates because the exposed surface area decreases and the material used as support can also interfere. In the last years, the use of magnetic materials to support photocatalysts has attracted special attention because it allows high surface areas to be exposed. Only few authors have reported the use of Ag3PO4/magnetic nanocomposites for photocatalysis and these need to be continued to improve their efficiency. In this work we synthesized Ag3PO4 and supported it on ferromagnetite (Fe3O4). In this study, Fe3O4 was synthesis following the Massart’s method. Ag3PO4 was synthesised over Fe3O4 from the reaction between silver nitrate (AgNO3) and disodium hydrogen phosphate (Na2HPO4). For characterization, DRS, SEM, XRD and magnetization studies were carried out. Ag3PO4 was synthesised and satisfactorily supported over magnetite (Fe3O423). The photodegradation of 10 mg·L−1 of methylene blue was achieved, although the apparent reaction rate constant was slightly lower for the magnetic composite than for bare Ag3PO4. This is explained because the composite contained 48% of the active Ag3PO4 material, as depicted form XRD studies.